External Shocks and Business Cycle Fluctuations in Mexico : How Important are U.S. Factors? - Sosa, Sebastian (IMF Working Papers; Working Paper ;, 2008)
This paper examines the relative importance of external shocks as sources of business cycle fluctuations in Mexico, and identifies the dynamic responses of domestic output to foreign disturbances. Using a VAR model with block exogeneity restrictions, it finds that U.S. shocks explain a large share of Mexico's macroeconomic fluctuations after NAFTA. This partly reflects greater trade integration-but also Mexico's "Great Moderation," as the country escaped its former pattern of macro-financial crises. In this period, Mexico's output fluctuations have been closely synchronized with the U.S. cycle, with a large and rapid impact of U.S. shocks on Mexican growth.